1996
DOI: 10.1046/j.1365-2559.1996.342383.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing epithelioid fibrosarcoma

Abstract: A case of sclerosing epithelioid fibrosarcoma arising in the thigh of a 40-year-old man is reported. This recently described sarcoma has a distinctive histological appearance which may cause confusion with a variety of other sarcomas with an epithelioid pattern, and indeed with benign soft tissue tumours showing hyalinization. Despite its bland cytology, sclerosing epithelioid fibrosarcoma is capable of metastases, often several years after surgical removal. The patient described here developed lung metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
2
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 0 publications
1
45
2
6
Order By: Relevance
“…Positive results were found in 81% of putative LGFMS and only 7 of 52 (13%) controls; of these seven positive non-LGFMS, four had been previously labeled 'SEF'. Along similar lines, one of the 4 genetically confirmed LGFMS reported by Reid et al 69 showed at least in part classical features of SEF. Rehki et al 70 also reported a hybrid SEF-LGMFS showing FUS rearrangement.…”
Section: Genetic Features and Relationship To Lgfmssupporting
confidence: 66%
“…Positive results were found in 81% of putative LGFMS and only 7 of 52 (13%) controls; of these seven positive non-LGFMS, four had been previously labeled 'SEF'. Along similar lines, one of the 4 genetically confirmed LGFMS reported by Reid et al 69 showed at least in part classical features of SEF. Rehki et al 70 also reported a hybrid SEF-LGMFS showing FUS rearrangement.…”
Section: Genetic Features and Relationship To Lgfmssupporting
confidence: 66%
“…[1][2][3] This case is unusual, however, in three respects. It has areas of high grade morphology with large zones of tumour necrosis, surrounded by highly cellular and mitotically active epithelioid areas.…”
Section: Discussionmentioning
confidence: 99%
“…1 3 5 In our case, not only were these areas more extensive, but they were surrounded by more obviously malignant epithelioid areas, indicative of a higher grade tumour, a feature not described previously. Indeed previous publications [1][2][3] have stressed relatively bland cytological features and the risk of erroneous benign diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All other purported positive markers have typically been either weakly, equivocally, or inconsistently expressed. Scattered, weak and inconsistent staining has been reported with CD34, S-100, CAM 5.2, bcl-2, and EMA [1,2,8,[12][13][14]. A positive CD99 stain led Folk et al [5] to perform RT-PCR for the t(11; 22)(q24; q12) translocation in two cases, which were both negative.…”
Section: Discussionmentioning
confidence: 99%